POLITIK HUKUM PENGUATAN FUNGSI LEGISLASI DEWAN PERWAKILAN DAERAH BERDASARKAN UUD NEGARA REPUBLIK INDONESIA TAHUN 1945 - Fernando Hasibuan; Hedwig Adianto Mau; Rotua Valentina Sagala (Journal of Innovation Research and Knowledge, 2025)
In Indonesia's constitutional system, the Regional Representative Council (DPD) plays a crucial role in representing regional interests. The legislative function of the DPD is explicitly regulated under Article 22D of the 1945 Constitution (third amendment). Although the DPD is granted the authority to propose and provide considerations on certain bills, the main issue lies in the limited scope of its authority, which does not include the final decision-making power in the legislative process. The theories employed in this study are the theory of legal politics and the theory of the constitution. The type of research in this study is categorized as normative or doctrinal legal research, involving a statutory approach and an analytical approach. The legal materials used are sourced from secondary data, comprising primary legal materials, secondary legal materials, and tertiary legal materials, collected through a literature review. The data analysis in this legal research employs a qualitative approach. The research findings indicate that the regulation of the DPD in the 1945 Constitution, the MD3 Law, and the P3 Law highlights its strategic role in proposing and providing input on bills related to regional interests, despite its limited authority often being overshadowed by the dominance of the House of Representatives (DPR). For instance, the MD3 Law, particularly Article 122, weakens the legislative function of the DPD by regulating the tasks and powers of the DPR without allocating adequate participation for the DPD in the legislative process. Furthermore, legal policy through Constitutional Court Decision No. 92/PUU-X/2012 has strengthened the legislative role of the DPD by recognizing its equal standing with the DPR and the President in proposing, discussing, and providing views on bills, particularly those concerning regional autonomy, central-regional relations, and fiscal balance, ensuring that national policies are more equitable and inclusive